2018
DOI: 10.3390/ijerph15050950
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Young People Who Self-Harm: A Review of Perspectives from Families and Young People

Abstract: Self-harm among young people remains largely stigmatised and misunderstood. Parents have been identified as key facilitators in the help-seeking process, yet they typically report feeling ill-equipped to support the young person in their care. The aim of this review was to examine the perspectives of both young people (aged 12–28) and parents and to develop the conceptual framework for a future qualitative study. A systematic search of MEDLINE and PsycINFO was performed to identify articles that focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 46 publications
(132 reference statements)
3
45
0
3
Order By: Relevance
“…Some parents reported having conversations about self-harm with their children, while others were uncertain and asked for information on how to do so effectively. According to young people themselves, parent's ability to "talk and listen" about self-harm is an effective support strategy [14]. In addition, our study participants emphasised another aspect of supportive communication, specifically, remaining calm and non-judgemental even during emotionally-charged situations with young people.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some parents reported having conversations about self-harm with their children, while others were uncertain and asked for information on how to do so effectively. According to young people themselves, parent's ability to "talk and listen" about self-harm is an effective support strategy [14]. In addition, our study participants emphasised another aspect of supportive communication, specifically, remaining calm and non-judgemental even during emotionally-charged situations with young people.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to parents in previous studies [15,16], our participants expressed a fear that setting boundaries could trigger another episode of self-harm and observed that siblings may feel neglected or become resentful of differential treatment of the young person who self-harms. These relational challenges reflect the need to equip parents, who are the primary source of help for young people [14,34], with the right support and resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 17% of adolescents and 13% of young adults (20% among university students) report a history of NSSI (Swannell, Martin, Page, Hasking, & St John, ). NSSI is associated with a range of negative consequences including permanent scarring (Lewis & Mehrabkhani, ), psychological distress for the individual as well as their friends and family (Curtis et al, ), and increased risk of future suicidal thoughts and behavior (Kiekens et al, ). Due to its prevalence and adverse outcomes, NSSI is listed as a condition requiring further study in the DSM‐5.…”
mentioning
confidence: 99%
“…Consideration of developmental factors may result in some negotiation between the practitioner and the young person regarding information to be disclosed to caregivers, whereby sensitive information (e.g., drug use) may be omitted. Consideration should also be given to the information and support resources available to caregivers (who may be experiencing significant guilt or anxiety given their young person's suicide risk), and the ability of caregivers to adequately respond to suicide risk and proactively engage crisis services (Curtis et al, ). Where suicide planning is identified, clinical monitoring should be maintained, either via increasing the frequency of face‐to‐face appointments, phone contact, or inpatient care.…”
Section: Recommended Approachmentioning
confidence: 99%